Morphological variability, mycelial compatibility and fungicidal sensitivity of Colletotrichum gloeosporioides causing leaf spot of ginger (Zingiber officinale Rosc.) - S J Ankegowda, C N Biju, C N Darshana, R Praveena, (Journal of Spices and Aromatic Crops, 2014)
Colletotrichum gloeosporioides isolates causing leaf spot of ginger were collected from diverse agroecological regions of Kodagu, Hassan, Shimoga and Chikmagalur districts of Karnataka (KAG 1-6) and Idukki and Wayanad districts of Kerala (KLG 1-3). Diversity analysis of the isolates revealed existence of considerable variability in the field populations of the leaf spot pathogen. Colour of the colony varied from white to dull grey and considerable variation was observed in the growth rate of the isolates. The conidial shapes varied with regions and were cylindrical with tapering ends, cylindrical, elliptical or dumbbell, whereas, most of the isolates belonged to cylindrical with tapering ends category. The appressoria were either unlobed, single lobed or multilobed. The size of conidia and appressoria ranged from 12.2-18.3 × 6.1-6.9 μM and 9.0-14.8 × 6.2-11.0 μM, respectively. Mycelial compatibility studies among the nine isolates revealed that, the isolate, KLG 3, originating from Kerala was most compatible with other isolates, while KLG 1 and KAG 6 exhibited a highly incompatible reaction. Microscopic observations to study the process involved in compatible reaction showed the aggregation of hyphae at region of contact, fusion of hyphae (formation of ‘H’ – like structure) and subsequent generation and growth of new hyphae from the point of contact. Among the fungicides tested at recommended dosages, propiconazole was found to be promising followed by carbendazim + mancozeb. The present study indicated that leaf spot caused by C. gloeosporioides is emerging as a major foliar disease in the ginger growing tracts.